2021
DOI: 10.5194/gmd-14-3769-2021
|View full text |Cite
|
Sign up to set email alerts
|

Development of a large-eddy simulation subgrid model based on artificial neural networks: a case study of turbulent channel flow

Abstract: Abstract. Atmospheric boundary layers and other wall-bounded flows are often simulated with the large-eddy simulation (LES) technique, which relies on subgrid-scale (SGS) models to parameterize the smallest scales. These SGS models often make strong simplifying assumptions. Also, they tend to interact with the discretization errors introduced by the popular LES approach where a staggered finite-volume grid acts as an implicit filter. We therefore developed an alternative LES SGS model based on artificial neura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…One approach is to train ML models to predict subgrid forcing (e.g., S q ) but incorporate a numerical divergence operation into their architectures (e.g., as the final layer of a neural network, see Zanna and Bolton [2020]). Another is to diagnose a different quantity whose divergence equals the subgrid forcing (Pawar et al., 2020; Stoffer et al., 2021; Yuval et al., 2021), train ML models to predict this quantity (i.e., the subgrid flux) directly, and compute divergences outside the learned model as part of the implementation of parameterization.…”
Section: Diagnosing Subgrid Forcingmentioning
confidence: 99%
“…One approach is to train ML models to predict subgrid forcing (e.g., S q ) but incorporate a numerical divergence operation into their architectures (e.g., as the final layer of a neural network, see Zanna and Bolton [2020]). Another is to diagnose a different quantity whose divergence equals the subgrid forcing (Pawar et al., 2020; Stoffer et al., 2021; Yuval et al., 2021), train ML models to predict this quantity (i.e., the subgrid flux) directly, and compute divergences outside the learned model as part of the implementation of parameterization.…”
Section: Diagnosing Subgrid Forcingmentioning
confidence: 99%
“…The performance of neural network-based SGS models is compared with the widely used dynamic Smagorinsky model (DSM) [61,62]. The a posteriori deployment is a rigorous task for any data-driven SGS model due to the presence of numerical instabilities, and the challenges and remedies have been highlighted in many studies [12,15,22,23,[86][87][88]. For example, Maulik et al [15] and Zhou et al [88] achieved the stable LES results by truncating SGS source term corresponding to negative eddy viscosity.…”
Section: B a Posteriori Deploymentmentioning
confidence: 99%
“…Guan et al [22] provided sufficient amount of data during training to obtain a stable a posteriori results. While the exact reason for this behavior is unknown, several issues such as error accumulation, aliasing errors, numerical instability, extrapolation beyond the training data, chaotic nature of turbulence, presence of multiple attractors might be responsible for unstable a posteriori simulation [6,23,38,87].…”
Section: B a Posteriori Deploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a priori (offline) tests, in which the accuracy of the SGS model in estimating the SGS term as a function of the resolved flow is evaluated, some of these studies have found the data-driven SGS models to accurately account for inter-scale transfers (including backscattering) and outperform physics-based models such as SMAG and DSMAG [7,56,75,120,122]. However, most of the same studies have also found that in a posteriori (online) tests, in which the data-driven SGS model is coupled with a coarse-resolution numerical solver, the LES model is unstable, leading to numerical blow-up or physically unrealistic flows [4,5,44,56,98,115,120,122]. While the reason(s) for these instabilities remain unclear, a number of remedies have been proposed, e.g., post-processing of the trained SGS model to remove backscattering or to attenuate the SGS feedback into the numerical solver, or combining the data-driven model with an eddy viscosity model [4,56,120,122] (also, see the excellent review by Beck and Kurz [5]).…”
Section: Introductionmentioning
confidence: 99%